Penta Helix Collaboration in Efforts to Prevent Child Abuse Cases in the City of Surabaya - Alfianingrum, Dinda; Anisykurlillah, Rosyidatuzzahro (Jurnal Kebijakan Publik, 2025)
Violence against children remains a critical issue in Indonesia, including in Surabaya, which, despite being awarded the title of World Child-Friendly City in 2024, continues to experience a yearly increase in reported cases. The main challenge lies in the weak cross-sectoral synergy in prevention efforts, highlighting the need for a collaborative approach. This study aims to analyze the implementation of the Penta Helix model in preventing child violence in Surabaya by involving five key actors: government, academia, business, community, and media. The research employed a qualitative descriptive method with a case study design. Subjects were selected through purposive sampling, including DP3APPKB Surabaya City, 17 August 1945 University Surabaya, PT Jasa Marga Surabaya-Mojokerto, the Surabaya Children's Forum, and Suara Surabaya Media. Data were collected through in-depth interviews, observation, and documentation, validated using triangulation, and analyzed using the Miles, Huberman, and Saldana interactive model. The findings reveal that the government acts as regulator and coordinator, academia contributes through research, education, and community service, business supports through capital assistance and CSR, the community especially the Surabaya Children's Forum actively engages in programs and campaigns, while the media disseminates information and provides public interaction space. The study concludes that Penta Helix collaboration contributes significantly to child violence prevention, although stronger coordination, expanded networks, and program sustainability remain necessary. The study implies that reinforcing cross-sectoral collaboration is essential to achieve more effective and sustainable child protection.